1988
DOI: 10.1073/pnas.85.23.9214
|View full text |Cite
|
Sign up to set email alerts
|

Formation of IgE-binding factors by T cells of patients infected with human immunodeficiency virus type 1.

Abstract: Peripheral blood mononuclear cells of 10 out of 26 patients with human immunodeficiency virus type 1 (HIV-1) released IgE-binding factors, as determined by two independent assays. The formation of the factors by the mononudear cells was enhanced by incubation of the cells with homologous IgE. In the presence of IgE, peripheral blood mononuclear cells from 15 of the 26 patients formed a detectable amount of IgE-binding factors, whereas those of normal individuals or allergic rhinitis patients failed to do so. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
2

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
1
21
2
Order By: Relevance
“…T cells from HTV-Iinfected patients were reported to release IgE BFs into their cultures (Carini et al, 1988). In the present study, however, the occurrence of FceRII on mononuclear cells from HTLV-Iinfected individuals was within normal range, and surprisingly, serum levels of IgE BFs were reduced in patients with ATL.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…T cells from HTV-Iinfected patients were reported to release IgE BFs into their cultures (Carini et al, 1988). In the present study, however, the occurrence of FceRII on mononuclear cells from HTLV-Iinfected individuals was within normal range, and surprisingly, serum levels of IgE BFs were reduced in patients with ATL.…”
Section: Discussioncontrasting
confidence: 47%
“…However, HTLV-Itransformed T cell line ED, which constitutively forms IgE BFs, responds to neither IL-4 nor IFN-y with enhanced biosynthesis of IgE BFs (Kawabe et al, 1988). Carini et al, (1988) reported that the culture supernatants of mononuclear cells from HIV-1-infected patients released another soluble factor that induced the formation of IgE BFs by normal human T cells. It is possible, therefore, that soluble factor(s) formed by mononuclear cells from HTLV-I-infected individuals may be involved in the formation of IgE BFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found complexed with IgE in the serum of atopic patients (7) and its level is highly elevated in patients with B-cell-derived chronic lymphocytic leukemia (19). Furthermore, T cells of patients infected with human immunodeficiency virus type 1 are induced to produce IgE-BF (20).…”
mentioning
confidence: 99%
“…Increased sCD23 in serum and synovial fluid in rheu matoid arthritis patients has been demonstrated [29], rais ing the question of the direct role o f sC'D23 in other dis eases. It has been previously reported that sCD23 is in creased in HI V-l infection [31][32][33][34], The fact that sCD23 has been reported to costimulate IFN-y production raises the possibility that sCD23 may play a pivotal role in the control of the immune response. Moreover, the receptors for IL-7 and CD23 have been found to be present lymphoid cells of HI V-l-infected subjects and on mitogen-stimulated T cells [25,26,[31][32][33][34].…”
mentioning
confidence: 99%